Anticonvulsant effects of ethanol stem bark extract of Lannea barteri (Anacardiaceae) in mice and chicks. (22nd August 2015) - Garba, K.; Yaro, A.H.; Ya'u, J.
Abstract: Ethnopharmacological relevance: Preparation of Lannea barteri is used in the treatment of epilepsy, gastritis, childhood convulsions among other uses in northern Nigeria for many years. The popularity of its efficacy is well established among the Traditional Medical Practitioners. Aim of the study: The present study aimed at screening the ethanol stem bark extract of Lannea barteri for possible anticonvulsant action. Materials and method: Anticonvulsant screening was carried out using pentylenetetrazole (PTZ), strychnine (STN) and picrotoxin (PTC) induced seizures in mice while Maximal electroshock (MES) test was carried out in day old chicks. Preliminary phytochemical screening of the extract was performed on the extract. The intraperitoneal median lethal dose (LD50 ) was carried out in mice. Results: The intraperitoneal ( i.p. ) LD50 of the extract was estimated to be 567.70 mg/kg in mice. Lannea barteri (160 mg/kg) significantly ( p ≤0.05) delayed the mean onset of seizures induced by PTZ when compared with normal saline treated group. Similarly, the extract at 160 mg/kg significantly ( p ≤0.05) prolonged the latency of convulsion induced by STN. Lannea barteri (40 mg/kg) significantly ( p ≤0.05) delayed the mean onset of seizures induced by picrotoxin in mice. The extracts at all the doses tested showed no observable effect in decreasing the mean recovery time of convulsed chicks in MEST. Flavonoids, alkaloids, tannins, saponins and glycosides were found present in the stem bark extract. Conclusion: Our findings revealed that the ethanol stem bark extract of Lannea barteri contained bioactive constituents that may be useful in the management of petit mal epilepsy and supports the ethnomedical claim for the use of its stem bark in the management of epilepsy. Graphical abstract: